(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The work is to analysis the structural stability and strength of a low budget Indian two wheeler TVS Sport bike alloy wheel rim in high speed conditions, the alloy wheel rim is holding the tyre and stability of the vehicle, the ANSYS Structural Analysis carried out for various RPM like 500, 1000, 1500 and 2000 RPM the results of stress, strain and deformation results taken for various materials like steel, aluminium and polypropylene